ANALISIS KEHANCURAN DAN KEMUNDURAN KERAJAAN SAFAWI - Muhammad Basri; Salsabila Siregar; Ririn Widayanti (CV. ADIBA AISHA AMIRA, 2024)
This research aims to analyze the phases of the downfall and decline of the Safavid Empire, a significant empire in the Persian region from the 16th to the early 18th century. In-depth analysis is conducted on political, economic, social, territorial changes, and power shifts that shaped the dynamics of the empire's destruction. The research also focuses on the impact of the Safavid downfall on the political structure and regional geography, including the formation of new nations. The literature review method is employed to construct a comprehensive historical narrative. The findings provide profound insights into the historical journey of the Safavid Empire and its significant consequences for the regional history of Persia